Chain-End Effect for Intermediate Water Formation of Poly(2-Methoxyethyl Acrylate) - Nishimura, S.; Ueda, T.; Murakami, D.; Tanaka, M. (Organic Materials, 2021)
Intermediate water (IW), which is formed not only by biocompatible polymers such as poly(2-methoxyethyl acrylate) (PMEA), but also by biomacromolecules, plays a key role in determining the biocompatibility of synthetic polymers. In this study, we compare the well-defined linear and cyclic PMEA using differential scanning calorimetry and atomic force microscopy. This study aims to clarify the role of the chain-end effect in IW formation to establish design guidelines for biomaterials.
Keywords: intermediate water; hydration state; chain-end effect; poly(2-methoxyethyl acrylate); cyclic polymers; interfacial structures